Students Learning Outcomes and Internalization Islamic Values in Buffer Solution Concept through Online Learning - Leny Heliawati; Anna Permanasari; Uun Sundari (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This study analyses students learning outcomes and internalization of Islamic values in buffer solutions through online learning during the Covid-19 pandemic. The study was conducted to find effective strategies in achieving students’ competence and Islamic values. This research is a quasi-experimental study conducted on 100 tenth-grade students using The One Group Pretest-Posttest model. The results showed students learning outcomes obtain an N-Gain value of 0.72 (high category). The internalization of Islamic values for three aspects: praying, blessing, and study hard determined the average above 3 (often do). Thus, the research concludes that online learning conducted on buffer materials is effective in mastering the content and internalization of Islamic values.